Accelerator‐driven high‐energy‐density physics: Status and chances. Issue 2 (27th December 2017) - Ren, J.; Maurer, C.; Katrik, P.; Lang, P.M.; Golubev, A.A.; Mintsev, V.; Zhao, Y.; Hoffmann, D.H.H.
Abstract : We review the development of high‐energy‐density physics (HEDP) driven by intense particle beams, and give an account of the current status and the anticipated developments in the near future. Since progress of this field is strongly coupled to the technical development of high‐current accelerators, we report on the recent results in specific areas of high‐current accelerators relevant to HEDP. These are related to dynamic vacuum problems and the activation of accelerator structural material by high‐current, high‐energy particle beams, and we give an example of dense plasma diagnostics with high‐energy protons. The reported results have been achieved at existing machines at the Gesellschaft für Schwerionenforschung (GSI‐Darmstadt), the Institute of Theoretical and Experimental Physics in Moscow (ITEP‐Moscow), and the Institute of Modern Physics (IMP‐Lanzhou), and they are relevant for facilities under construction such as the FAIR facility in Darmstadt and the High Intensity Accelerator Facility (HIAF) proposed in China.